A Bibliometric Analysis: Computer Science Research From Indonesia - Edi Supriyadi (Universitas Pendidikan Nasional, 2022)
Bibliometric indicators originally counted ways to measure research quality. This endured for decades following the term's introduction. The purpose of this research is to carry out a bibliometric analysis of the present status and trends in computer science articles written by Indonesian authors that are included in the Scopus database. Bibliographic indicators were analyzed using SciVal (www.scival.com). Elsevier constructed SciVal using Collexis' semantic technology after buying it in 2010. SciVal evaluates scientific performance using Scopus and tracks funding. Between the years 1998 and 2022, the total number of indexed papers in Scopus that discuss the advancement of research outcomes in computer science has greatly expanded. This rise reached its highest point in 2019, with 121 publications. Santoso is the most prolific Indonesian researcher when it comes to releasing research results on computer science in Indonesia. The University of Indonesia has been the most helpful sponsor in terms of sponsoring computer science research.